2022
DOI: 10.3390/cryst12050591
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Preparation Process and Performance of a Wear-Resistant and Corrosion-Resistant Coating

Abstract: In order to study the wear resistance and corrosion resistance of a composite material with a Fe316L substrate and Co-Cr-WC coating, Co-Cr alloy coatings with different mass fractions of WC (hard tungsten carbide) were prepared on a Fe316L substrate by laser cladding technology. The phase composition, microstructure and element distribution were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The hardness of the samples was tested by a Vickers m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the contrary, introduction of WC into a Co-Cr matrix led to a significant decrease in corrosion current density, from 3 × 10 −3 to 4 × 10 −4 A/cm 2 , compared to non-modified Co-Cr matrix, due to the pronounced passivation effect of WC particles. However, corrosion potential decreased from 350 to 70 Mv [22].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the contrary, introduction of WC into a Co-Cr matrix led to a significant decrease in corrosion current density, from 3 × 10 −3 to 4 × 10 −4 A/cm 2 , compared to non-modified Co-Cr matrix, due to the pronounced passivation effect of WC particles. However, corrosion potential decreased from 350 to 70 Mv [22].…”
Section: Introductionmentioning
confidence: 94%
“…Coatings based on carbides [15,16], nitrides [17,18] and carbonitrides [19] of transition metals, such as TiC, TaC, WC, TaN, and Ti(C, N), are widely used to improve surface properties under wear and corrosion conditions, due to their high hardness, low friction coefficient and high chemical stability. Many authors have demonstrated that the introduction of such hard particles in corrosion-resistant metal matrices leads to the enhancement of hardness and strength [20], wear and erosion resistance [21], and corrosion resistance [22]. However, choosing the right hardening particles for each matrix is crucial for the corrosion behavior of the composites in terms of matching the corrosion potentials of the reinforcing particles and the metal matrix [23].…”
Section: Introductionmentioning
confidence: 99%